Design of a green supply chain network by considering the possibility of storage and location-routing problem under uncertainty. Issue 2 (2nd September 2019) - Khalafi, Saeede; Zarei, Mahnaz
In the literature of operations research, the subject of transportation of products and services and specifically, the vehicle routing problem (VRP) have always been on priority as an important field of study. To date, a large number of studies have been done in the field of VRP and its different types, but only few of them have looked at the problem from the perspective of environmental factors. In this paper, considering the importance of environmental issues, a model has been designed for a single-objective green routing problem. Such items as discount, heterogeneous vehicles and multi-depot distribution centres have been considered in this model, which has been designed in the form of a multi-product and multi-periodic model. Then, the effectiveness of the proposed model was illustrated using the problems generated in different dimensions by means of GAMS software. At the end, the accuracy of the proposed model under uncertainty was evaluated through sensitivity analysis and the obtained results were indicative of the effectiveness and efficiency of the proposed model.